Dual Interlocked Mediators Enable Single-Ion-Conducting Quasi-Solid-State Electrolytes for Ultrafast-Charging Long-Life Sodium Metal Batteries - Zhang, Yuan; Pan, Long; Leong, Cheong Wa; Qi, Xing‑Guo; Huang, Xiaozhong; Cai, Xinyi; Cao, Mufan; Gao, Min; Zhang, Haoyu; Sha, Dawei; Zhou, Yang; Sun, ZhengMing (Nano-Micro Letters, 2026)
Quasi-solid-state electrolytes (QSEs) are critical for ultrafast-charging yet high-safety sodium metal batteries (SMBs), yet their implementation is hindered by sluggish Na+ transport in bulk and at interfaces. Here, we propose dual interlocked mediator engineering that transcends conventional independent approaches by coupling cationic Sn2+ salt with anionic difluoro(oxalato)borate (DFOB⁻) salts to simultaneously regulating bulk ion transport and bilateral interface chemistry. During QSE preparation, Sn2+ initiates in situ cationic polymerization, while DFOB⁻ acts as a retarding agent to suppress runaway polymerization. The first interlocking effect in the Sn-FB QSE bulk builds a uniform network, enabling near-unity Na+ transference number (0.94) and robust puncture strength (8.5 kPa). During cell operation, Sn2+ is reduced to form a hybrid NaSn alloy-based solid-electrolyte interphase, while DFOB⁻ oxidizes to generate a robust yet thin cathode–electrolyte interphase, respectively. This second interlocking effect creates adaptable bilateral interphases that facilitate Na+ diffusion and mitigate interfacial degradation. As a result, the symmetric cells exhibit 6000 h stability, and full cells retain 80.1 mAh g–1 at an ultrafast-charging rate of 15C and retain 90% capacity at 3C over 2000 cycles. Furthermore, high-mass-loading full cells and pressure-free pouch cells are demonstrated, underscoring the potential of dual interlocked mediator engineering for practical SMBs. Highlights: 1 Single-ion conduction. Sn-FB quasi-solid-state electrolytes (QSEs) achieves near-unity Na+ transference number (0.94) and high conductivity (1.3 mS cm–1) via synergistic Sn2+ initiated polymerization and difluoro(oxalato)borate (DFOB⁻) retardation. 2 Highly adaptable bilateral interphases. Sn2+ was reduced to form a hybrid NaSn alloy/inorganic-rich solid-electrolyte interphase to homogenize electric fields, while DFOB– was oxidized to form robust, yet thin cathode–electrolyte interphase for rapid interfacial kinetics. 3 Superior electrochemical performances. Sn-FB QSE delivers 6000 h stability without dendrite and retains 90% capacity after 2000 cycles at 3C.